2023
DOI: 10.1007/s12015-023-10539-9
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Mechanisms and Therapeutic Potential of Mesenchymal Stem Cells

Abstract: Mesenchymal stem cells (MSCs) are regarded as highly promising cells for allogeneic cell therapy, owing to their multipotent nature and ability to display potent and varied functions in different diseases. The functions of MSCs, including native immunomodulation, high self-renewal characteristic, and secretory and trophic properties, can be employed to improve the immune-modulatory functions in diseases. MSCs impact most immune cells by directly contacting and/or secreting positive microenvironmental factors t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 191 publications
0
8
0
Order By: Relevance
“…Numerous studies have reported on the success of the MSC therapeutic effect in inflammatory regulation [ 52 ] as well as the amelioration of neuropathology in HD [ 53 , 54 , 55 ]. We applied bone marrow-derived mouse MSCs for the treatment of R6/2 mice via intravenous administration, which has demonstrated to be the best delivery route of MSCs for improving liver function [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have reported on the success of the MSC therapeutic effect in inflammatory regulation [ 52 ] as well as the amelioration of neuropathology in HD [ 53 , 54 , 55 ]. We applied bone marrow-derived mouse MSCs for the treatment of R6/2 mice via intravenous administration, which has demonstrated to be the best delivery route of MSCs for improving liver function [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Quantification of mRNA levels showed that the expression level of the Adgre1 gene (encoding protein F4/80) was slightly increased in R6/2-PBS mice vs. WT-PBS mice ( p = 0.0591), while the reduction in R6/2-MSC mice vs. R6/2-PBS mice was highly significant ( p < 0.0001) ( Figure 4 A,B). Furthermore, we analyzed mRNA levels of Cd206 , Cd68 and Cd163 , markers of the M2-type (anti-inflammation) macrophage, where MSCs promote polarization [ 52 ] and in turn increase the population. In all these markers, we did not find any differences in either the R6/2-PBS mice vs. WT-PBS comparisons or between the two R6/2 treatment groups ( Figure 4 C).…”
Section: Resultsmentioning
confidence: 99%
“…Five decades ago, MSCs were first recognized for their pluripotent potential, and recent findings suggest their regenerative and modulatory properties [ 296 ]. MSCs are the source of a myriad of active molecules [ 297 ]. However, concerns about the safety of cell-based therapies still challenge the applicability of MSCs for use in humans [ 298 ].…”
Section: Pharmacology Of Extracellular Vesiclesmentioning
confidence: 99%
“…Several studies have investigated MSCs' immunology and their potential to evade and/or influence the immune system of the host [54]. This is in relation to both immunosuppression and/or immunoprivilege.…”
Section: Msc Immunomodulation and Advanced Medicinal Therapymentioning
confidence: 99%